Will the EU Disintegrate? What Does the Likely Possibility of Disintegration Tell About the Future of the World?. Issue 1 (2nd January 2017) - Patomäki, Heikki
Abstract: Is it true that either the EU will be democratised or it will disintegrate? I concur that the current policies, principles, and institutions of the EU both generate counterproductive politico-economic effects and suffer from problems of legitimation. These effects and problems, which are not confined to Europe, give rise to tendencies towards disintegration. My second point concerns the timing of the required learning and reforms. Modest policy proposals and tentative steps within the existing EU Treaty framework may be too little too late. The question is whether there is enough time for deeper transformations in Europe—and also globally.